Intravenous versus Oral Iron for Iron-Deficiency Anemia in Pregnancy (IVIDA): A Randomized Controlled Trial - Lewkowitz, Adam K.; Stout, Molly J.; Cooke, Emily; Deoni, Seon C.; D'Sa, Viren; Rouse, Dwight J.; Carter, Ebony B.; Tuuli, Methodius G. (American Journal of Perinatology, 2021)
Objective Iron-deficiency anemia (IDA) can have serious consequences for mothers and babies. Iron supplementation is recommended, but the administration route is controversial. We sought to conduct a randomized controlled trial (RCT) testing the effectiveness and safety of intravenous (IV) iron compared with oral iron on perinatal outcomes in pregnant women with IDA.Study Design This open-label RCT randomized patients with IDA (hemoglobin [hgb] <10 g/dL and ferritin <30 ng/mL) at 24 to 34 weeks' to oral iron or single 1,000-mg dose of IV low-molecular weight iron dextran over one hour. The primary outcome was maternal anemia at delivery (hgb < 11 g/dL). Secondary outcomes were mild/moderate or severe adverse reactions, maternal hgb and ferritin at delivery, blood transfusion, gestational age at delivery, birth weight, neonatal hgb and ferritin, and composite neonatal morbidity. Analysis was as per protocol.Results The trial was stopped early for logistical reasons, and the data analyzed as preliminary data to inform a larger, potentially externally funded, definitive trial. Of 55 patients approached, 38 consented. Of these, 15 were withdrawn: 5 received IV iron from their primary obstetrician after being randomized to oral iron and 10 declined to receive IV iron. Of the remaining 23 patients, who were included in the analytic population, 13 received oral iron and 10 received IV iron. The rate of maternal anemia at delivery (hgb < 11 g/dL) was high overall but significantly reduced with IV iron (40 vs. 85%, p = 0.039). Rates of maternal hgb < 10 g/dL were significantly lower in the IV iron group (10 vs. 54%, p = 0.029). There were no severe adverse reactions and similar rates of mild/moderate reactions between groups.Conclusion IV iron reduces rates of anemia at the time of admission for delivery, supporting a larger RCT comparing IV versus oral iron for the treatment of IDA of pregnancy powered for definitive clinical outcomes. However, issues uncovered in this RCT suggest that patient, clinician, and systems-level barriers associated with different IDA treatment modalities must be considered prior to conducting a larger RCT. This study is registered with clinicaltrials.gov with identifier no.: NCT03438227.Key Points
Keywords: iron-deficiency anemia; pregnancy; intravenous iron; oral iron